National Resistance Trends in Azerbaijani Literature - Rustamkhanli, Tanzila (Scholarya Demo Journal of Ruby, 2019)
The socio-political, literary-theoretical and artistic-aesthetic idea of Azerbaijan could benefit from the Russian language and its approach to Europe within Russia, bringing the progressive ideals of the West into society. However, at that time Russia was using all means to distinguish its colony from historical roots. We need to review some historical facts: From the beginning of the 19th century, it was forbidden to use the word Azerbaijan to suppress the resistance of the population of Northern Azerbaijan. The activities of tsarism in the above-mentioned areas were unequivocal: at the first stage of Russia’sconsolidation of their positions in Azerbaijan, Armenians, Germans, Poles weretransferred to these lands and tried to satisfy their interests by creating acommon Christian-Muslim confrontation. The Russian government was lured by the use of force and resistance. Despite all this, there were rebels in everypart of northern Azerbaijan, protests, and resistance movements. Although the Russians maneuvered during the occupation, they could not avoid bloodshed and massacres, and the local people had to face the battlefields. Russia was trying to take advantage of the tense situation in the international arena, theweakening of the Ottoman Empire, which lost its opportunity to intervene inthe events of the South Caucasus and had been heavily defeated by Russia inthe second half of the eighteenth century and caused strengthening of tsarism.